2022
DOI: 10.3390/axioms11080369
|View full text |Cite
|
Sign up to set email alerts
|

Sharp Bounds for the Second Hankel Determinant of Logarithmic Coefficients for Strongly Starlike and Strongly Convex Functions

Abstract: The logarithmic coefficients are very essential in the problems of univalent functions theory. The importance of the logarithmic coefficients is due to the fact that the bounds on logarithmic coefficients of f can transfer to the Taylor coefficients of univalent functions themselves or to their powers, via the Lebedev–Milin inequalities; therefore, it is interesting to investigate the Hankel determinant whose entries are logarithmic coefficients. The main purpose of this paper is to obtain the sharp bounds for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Recent studies, like [49], have shown that the classes could be studied further when the strong starlikeness of order α of the operator (λ, q)-fractional differintegral operator can be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, like [49], have shown that the classes could be studied further when the strong starlikeness of order α of the operator (λ, q)-fractional differintegral operator can be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the importance of the logarithmic coefficients, in reference [8], Sevtap Sümer Eker, Bilal Şeker, Bilal Çekiç, and Mugur Acu obtain the sharp bounds for the second Hankel determinant concerning the logarithmic coefficients of strongly starlike functions and strongly convex functions. The results presented here could inspire further studies that focus on other subclasses of univalent functions and obtain the boundaries for higher-order Hankel determinants.…”
Section: Overview Of the Published Papersmentioning
confidence: 99%
“…For further investigations of the Hankel determinant on logarithmic coefficients, see [57][58][59][60]. In this section, we compute the sharp estimates of logarithmic coefficients up to µ 3 and Fekete-Szegö, Zalcman, and Krushkal inequalities along with the Hankel determinant H 2,1 G g /2 for the class SS * SG .…”
Section: Logarithmic Coefficientmentioning
confidence: 99%